Cartilage evaluation by ultrasonography in patients with rheumatoid arthritis: a scoping review - Takehisa Ogura; Takaharu Katagiri; Hideto Kameda (BMC, 2023)
Abstract Background This study aimed to provide an overview of ultrasonographic cartilage evaluation in patients with rheumatoid arthritis (RA) and identify research gaps in the utilization of cartilage evaluation. Methods The study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines. A systematic literature search of the PubMed, Embase, and Cochrane Library databases was conducted for articles published up to July 2022 using the search term variations of "cartilage," "ultrasonography," and "rheumatoid arthritis." Studies that included patients with RA who underwent cartilage evaluation by ultrasonography were selected. Articles published in languages other than English and about juvenile idiopathic arthritis were excluded. Results Twenty-nine articles were identified. Most were cross-sectional studies (86%), mainly involving the metacarpophalangeal (55%) and knee (34%) joints. Assessments were performed using quantitative, binary, and semi-quantitative methods in 15, 10, and 15 studies, respectively. Reliability assessments were conducted in 10 studies, which showed feasible reliability but were limited to the finger joints. The validity assessment was validated in one study each that compared cartilage thickness measurements with cadaveric specimens and histological and semi-quantitative methods with surgical specimens, respectively. Comparisons with conventional radiography were also performed in six studies, which showed significant correlations. However, there was heterogeneity in the examination and assessment methods, and no adequate longitudinal evaluation was conducted. Conclusion This review highlights the need for further research and validation of ultrasonographic cartilage assessment in patients with RA.